Dissection of CD20 regulation in lymphoma using RNAi - Słabicki, Mikołaj; Jethwa, Alexander; Sellner, Leopold; Walther, Thomas; Hüllein, Jennifer; Dietrich, Sascha; Mamidi, Srinivas; Kirschfink, Michael; Fröhling, Stefan; Zenz, Thorsten (Leukemia, 2016)
Leukemia is one of the leading journals in hematology and oncology. It is published monthly and covers all aspects of the research and treatment of leukemia and allied diseases. Studies of normal hemopoiesis are covered because of their comparative relevance.
Gesehen am 24.10.2017